2020
DOI: 10.3390/s20215997
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Mitigation of RPL Rank and Version Number Attacks in the Internet of Things: SRPL-RP

Abstract: The rapid growth of the Internet of Things (IoT) and the massive propagation of wireless technologies has revealed recent opportunities for development in various domains of real life, such as smart cities and E-Health applications. A slight defense against different forms of attack is offered for the current secure and lightweight Routing Protocol for Low Power and Lossy Networks (RPL) of IoT resource-constrained devices. Data packets are highly likely to be exposed in transmission during data packet routing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…A secure RPL routing protocol (SRPL-RP) for identifying and isolating rank and version attacks was proposed in [26]. The authors extended the work in [21,27] in which mitigation methods identified both rank and version attacks.…”
Section: Trust and Protocol-based Mitigation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A secure RPL routing protocol (SRPL-RP) for identifying and isolating rank and version attacks was proposed in [26]. The authors extended the work in [21,27] in which mitigation methods identified both rank and version attacks.…”
Section: Trust and Protocol-based Mitigation Methodsmentioning
confidence: 99%
“…In Table 6, a comparison of our work with four similar studies is presented. Specifically, the evaluation results from the studies of MRTS [24], SRPL-RP [26], and SecTrust-RPL [26,28] are compared with our proposed SRF-IoT framework. The metrics used in the comparison are the PDR, parent switches, and packets dropped.…”
Section: Comparison With Related Workmentioning
confidence: 99%
“…Furthermore, the packet forwarding process in IoT-constrained devices is influenced by potential security threats, affecting the delivered services to end-users as the performance of the malignant nodes is rapidly increased during the data packet routing process. Eventually, the network's topology will be disrupted, and the resulting overhead will deplete the nodes' power resources and eventually break down the whole network [20].…”
Section: Security Issues and Threats In The Rpl Protocolmentioning
confidence: 99%
“…A security solution for RPL called SRPL‐RP is presented in Almusaylim et al 20 The solution attempts to detect and isolate malicious nodes that directly modify the rank and the version number values by using a DIO message timestamp threshold in the network. Zaminkar et al 21 proposed a scheme for the detection and elimination of sinkhole attack in the RPL protocol, called SOS‐RPL.…”
Section: Related Workmentioning
confidence: 99%